Determination of 23 perfluorinated alkylated substances in water and suspended particles by ultra-performance liquid chromatography/tandem mass spectrometry. Issue 14 (6th December 2018) - Wang, X.F.; Wang, Q.; Li, Z.G.; Huang, K.; Li, L.D.; Zhao, D.H.
Abstract: A practical multi-residue method based on ultra-performance liquid chromatography/tandem mass spectrometry was developed for the simultaneous determination of 23 perfluorinated alkylated substances (PFASs) in water and suspended particles. Suspended particle samples were extracted with 1% formic acid–acetonitrile and cleaned by matrix solid phase dispersion extraction using a C18 sorbent and graphitized carbon black. Water samples were filtered through 0.7-μm glass fiber membranes and enriched utilizing weak anion exchange cartridges. The eluent was dried under a gentle stream of N2 at 45° C and suspended in 1 mL acetonitrile–5 mM ammonium acetate (1:1, vol:vol). Gradient elution for chromatographic separation utilized acetonitrile and 5 mM ammonium acetate as mobile phases on a reverse phase C18 column. The compounds were quantified using an internal standard method in multiple reaction-monitoring mode. Limits of detection and quantitation of the 23 PFAS test compounds in water samples were 0.5–10 ng L −1 and 2–20 ng L –1, respectively. Recoveries at three fortified levels of 20, 50, and 200 ng L –1 ranged from 68.5% to 118% with relative standard deviations below 9.6%. We used this method to determine PFAS levels in real water and suspended particle samples and found high sensitivity and good reproducibility.